1996
DOI: 10.1002/(sici)1097-0118(199602)21:2<113::aid-jgt1>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Well covered simplicial, chordal, and circular arc graphs

Abstract: A graph G is called well covered if every two maximal independent sets of G have the same number of vertices. In this paper, we characterize well covered simplicial, chordal and circular arc graphs. © 1996 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…Thus, Theorem 3.1 yields the following. Recall that, as noted in Table 1, it follows from results of Prisner et al [36] that localizable graphs can be recognized in polynomial time within the class of chordal graphs (and, more generally, also in the class of C 4 -free graphs [24]).…”
Section: A Hardness Proof and Its Implicationsmentioning
confidence: 95%
“…Thus, Theorem 3.1 yields the following. Recall that, as noted in Table 1, it follows from results of Prisner et al [36] that localizable graphs can be recognized in polynomial time within the class of chordal graphs (and, more generally, also in the class of C 4 -free graphs [24]).…”
Section: A Hardness Proof and Its Implicationsmentioning
confidence: 95%
“…Recall that a simplicial vertex is one whose neighborhood is complete. Prisner, Topp, and Vestergaard [5] considered simplicial vertices in well-covered graphs. In particular, they defined a simplex as a maximal clique containing a simplicial vertex, and showed that if a graph is well-covered then the simplices are vertex-disjoint, and if every vertex belongs to exactly one simplex then the graph is well-covered.…”
Section: Triangles and Simplicial Verticesmentioning
confidence: 99%
“…9 if S * is not independent then 10 return ∅. 11 Construct the graph H * x . 12 Construct the flow network F…”
Section: Algorithmmentioning
confidence: 99%